A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia - Retzer, Michael E. (Zootaxa, 2006)
Farlowella altocorpus is described from six specimens from a single locality on the Río Coroico, a tributary of the Río Beni in Bolivia. Farlowella altocorpus is a member of the Farlowella nattereri Steindachner species group and can be distinguished from other members of that group by a unique combination of characters: snout tip to mouth length 73–87% of pectoral fin length in adults, body depth 69–79% of pelvic fin length, body depth 49–53% of distance between pelvic and pectoral fins, head length 1.94–2.28 times length of snout tip to mouth, mid-ventral plates keeled, pectoral fins reach origins of pelvic fins, not having first anal and dorsal fin spines entirely darkly pigmented, anterior median lateral plates 14–16, posterior median lateral plates 16–18, post-anal plates 22–23, and abdominal plates 22–31.